BPSK Modulation and Demodulation with Power Line Carrier Communication and GSM Communication for Smart Metering - B V Rajanna; SVNL Lalitha; Ganta Joga Rao; S K Shrivastava (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
GSM/GPRS and PLC communication are used for Automatic Meter Reading (AMR) applications. These AMR systems have made substantial progress over the recent years in terms of functionality, scalability, performance and openness such that they can perform remote metering applications for very demanding and complex systems. By using BPSK (Binary Phase Shift Keying) modulation with Power Line Carrier Communication, Smart Metering can be done in Rural Smart Micro-grids. The design and Simulation of BPSK Modulation and Demodulation are successfully done by using MATLAB/Simulink software. The advantages of using BPSK modulation over the QPSK modulation and the advantages of PLC Communication over the GSM Communication is identified in this paper.